Elements of a design method – a basis for describing and evaluating design methods. (5th December 2022) - Gericke, Kilian; Eckert, Claudia; Stacey, Martin
Abstract: Method development is at the heart of design research as methods are a formalised way to express knowledge about how aspects of design could or should be done. However, assuring that methods are in fact used in industry has remained a challenge. Industry will only use methods that they can understand and that they feel will give them benefit reliably. To understand the challenges involved in adopting a method, the method needs to be seen in context: it does not exist in isolation but forms a part of an ecosystem of methods for tackling related design problems. A method depends on the knowledge and skills of the practitioners using it: while a description of a method is an artefact that is a formalisation of engineering knowledge, a method in use constitutes a socio-technical system depending on the interaction of human participants with each other as well as with the description of the method, representations of design information and, often, tools for carrying out the method's tasks. This paper argues that crucial factors in the adoption of methods include how well they are described and how convincingly they are evaluated. The description of a method should cover its core idea, the representations in which design information is described, the procedure to be followed, its intended use, and the tools it uses. The account of a method's intended use should cover its purpose, the situations or product types within its scope, its coverage of kinds of problems within its scope, its expected benefit and conditions for its use. The different elements need to be evaluated separately as well as the method as an integrated whole. While verification and validation are important for some elements of methods, it is rarely possible to prove the validity of a method. Rather the developers of methods need to gather sufficient evidence that a method will work within a clearly articulated scope. Most design methods do not have binary success criteria, and their usefulness in practice depends as much on simplicity and usability as on the outcomes they produce. Evaluation should focus on how well they work, and how they can be customised and improved.